Cyclists' rights to the city: The realisation of cyclists' rights in the city of Johannesburg - Suleman, Muhammed (Department of Civil Engineering, 2019)
This research follows from the announcement of the Johannesburg mayor to stop the development of cycle lanes in the city of Johannesburg. The research is based on the notion that cyclists, like all other road users, have an equal right to the city. Therefore, planning for cyclists in cities should be awarded the same level of importance as planning for other modes of transport. However, having a right to city is, to a large extent, controlled by those who plan and shape the city. For this reason, the research places planning at the centre of the process, and unpacks the role of transport planners in shaping the city as a cycle friendly space. In doing this, the research focuses on the city of Johannesburg, a city which has, between 2007 and 2018, seen the development of 40kms of dedicated cycle lanes. The City decided to stop the development of cycle lanes because the city has not experienced an increase in cycling mode share. The research suggests that it is too early in the project to stop cycling development in Johannesburg. The city needs to relook at what has been done, find the gaps, and improve the programme. The research conducts a case study evaluation. The method focuses on four areas in Johannesburg in which cycle lanes have been constructed. Through an interview process, the research discusses why, transport planners feel cycling has not increased in Johannesburg, despite the interventions by the city in these four areas. The perspective of the transport planners are then compared to a range of articles relating to the development of the cycle lanes in Johannesburg. The research finds that while there is an acknowledgement of the city’s efforts to develop cycle lanes, there is a problem with the planning process. To understand the planning process better, the research discusses six international precedent cities, which have successfully increased cycling mode share. Through unpacking the planning process in these international cities, the research demonstrates the impacts that, the correct planning process can have, in the promotion of cyclists’ rights in cities. The research identifies certain gaps in the Johannesburg planning process. The research highlights a range of strategies which planners need to focus on in Johannesburg. However, at the root of it all, the research finds that cycling development in Johannesburg did not follow any specific cycling plan, while international best practice indicates that this is a major requirement. There is no clear guideline or strategy from the city which planners are following and, therefore, there is no coherent or complete plan for promoting cycling in Johannesburg.